2011
DOI: 10.1073/pnas.1104923108
|View full text |Cite
|
Sign up to set email alerts
|

Observations of nucleation of new particles in a volcanic plume

Abstract: Volcanic eruptions caused major weather and climatic changes on timescales ranging from hours to centuries in the past. Volcanic particles are injected in the atmosphere both as primary particles rapidly deposited due to their large sizes on time scales of minutes to a few weeks in the troposphere, and secondary particles mainly derived from the oxidation of sulfur dioxide. These particles are responsible for the atmospheric cooling observed at both regional and global scales following large volcanic eruptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 30 publications
5
45
3
Order By: Relevance
“…In addition, concentrations of the total number of particles (Diameter > 10 nm) measured by the CPC 3010 increased significantly. This was related to sulphuric acid droplet nucleation events as suggested by Schumann et al (2011) and shown by Boulon et al (2011). Altogether, these data clearly indicate that volcanic ash were present in the boundary layer at the PdD station.…”
Section: In-situ Measurements At Pddsupporting
confidence: 57%
“…In addition, concentrations of the total number of particles (Diameter > 10 nm) measured by the CPC 3010 increased significantly. This was related to sulphuric acid droplet nucleation events as suggested by Schumann et al (2011) and shown by Boulon et al (2011). Altogether, these data clearly indicate that volcanic ash were present in the boundary layer at the PdD station.…”
Section: In-situ Measurements At Pddsupporting
confidence: 57%
“…We found that including BLN reduces the relative increase in CDNC due to volcanic degassing because baseline CDNC are higher than in the PD no vol run that neglected BLN. Consequently, we calculate a global annual mean cloud albedo effect that is ∼12 % lower than that calculated for the PD runs without BLN, which is in contrast to what has been concluded by Boulon et al (2011). Clearly, Boulon et al (2011) made an important observation, however as long as we do not fully understand the precise nucleation mechanism operating, no conclusive statement can be made regarding the importance of BLN in affecting the magnitude of the climate impact of volcanic degassing.…”
Section: Discussioncontrasting
confidence: 46%
“…Therefore, the comparison of our model estimate to the Yuan et al (2011) study is for qualitative purposes only. Boulon et al (2011) suggested that using a binary homogeneous H 2 SO 4 -H 2 O nucleation scheme (Kulmala et al, 1998), as has been done in our study, will underestimate the climate impact induced by volcanic degassing because these authors observed very high nucleation rates in the boundary layer following the 2010 Eyjafjallajökull eruption. We carried out additional PD runs that included a widely used empirical approach to account for boundary layer nucleation (BLN) (e.g., Spracklen et al, 2006Spracklen et al, , 2010Merikanto et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Schumann et al (2011) found the same fine secondary particles adhering to the surfaces of many coarse particles. In the presence of a large number of pre-existing ash particles, in fact, the energetically favoured path for gases is to condense onto particle surfaces, rather than forming new ones through the nucleation of sulphuric acid droplets, as suggested by Schumann et al (2011) and shown by Boulon et al (2011). We argue that, in this process, the large number of coarse particles observed on 18 May, 3 times higher than in April (Fig.…”
Section: Case 2: 18-20 May 2010mentioning
confidence: 73%